2001
DOI: 10.1051/0004-6361:20010959
|View full text |Cite
|
Sign up to set email alerts
|

Line ratios for helium-like ions: Applications to collision-dominated plasmas

Abstract: Abstract. The line ratios R and G of the three main lines of He-like ions (triplet: resonance, intercombination, forbidden lines) are calculated for C v, N vi, O vii, Ne ix, Mg xi, and Si xiii. These ratios can be used to derive electron density ne and temperature Te of hot late-type stellar coronae and O, B stars from high-resolution spectra obtained with Chandra (LETGS, HETGS) and XMM-Newton (RGS). All excitation and radiative processes between the levels and the effect of upper-level cascades from collision… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
327
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(350 citation statements)
references
References 47 publications
(55 reference statements)
19
327
2
Order By: Relevance
“…This value is better constrained than in Paper I because of the higher S/N of the RGS spectrum analysed here. Comparing this ratio with the tables of Porquet et al (2001) and with the radial dependence of the f /i ratio shown in Fig. 4 of Paper I indicates that the Ne ix lines must form in a harsh UV radiation field.…”
Section: High-resolution X-ray Spectroscopysupporting
confidence: 60%
See 1 more Smart Citation
“…This value is better constrained than in Paper I because of the higher S/N of the RGS spectrum analysed here. Comparing this ratio with the tables of Porquet et al (2001) and with the radial dependence of the f /i ratio shown in Fig. 4 of Paper I indicates that the Ne ix lines must form in a harsh UV radiation field.…”
Section: High-resolution X-ray Spectroscopysupporting
confidence: 60%
“…The He-like triplets, which consist of a resonance line (r), an intercombination doublet (i), and a forbidden line ( f ), can be used as a diagnostic of the UV radiation field in the region of the X-ray plasma (for details see Gabriel & Jordan 1969;Blumenthal et al 1972;Porquet et al 2001). The RGS spectrum of 9 Sgr indicates that the empirical f /i intensity ratios are strongly reduced compared to the ratios of the transition probabilities.…”
Section: High-resolution X-ray Spectroscopymentioning
confidence: 99%
“…For example, if collisions are dominant, the ratio G = (i + f )/r ∼ 1 obtains, whereas if photoionizations dominate the exitation G ∼ 4 (e.g. Porquet & Dubau 2000;Porquet et al 2001). From the O VII f ir complex in our XMM-Newton spectrum, we estimate G ∼ 0.9 ± 0.1 for γ Cas.…”
Section: Helium-like Diagnostics Of Electron Densitiesmentioning
confidence: 76%
“…O vii traces the location of plasma at temperatures around 2 MK, and its forbidden ( f ) to intercombination (i) line ratio is sensitive to density and UV radiation, specifically one finds f /i = R 0 /(1 + φ/φ c + n e /n c ), see, e.g. Mewe & Schrijver (1978); Porquet et al (2001). In the low-density case (n e < ∼ 10 10 cm −3 ) additional photons in the i-line are only due to the radiation term φ/φ c .…”
Section: The High Resolution X-ray Spectrummentioning
confidence: 99%